VIRTUAL REFERENCE SERVICES: TOOLS AND TECHNIQUES - BARDHANARYA, Research Scholar, Harsh; MISHRA, Reader, Dr. J.K.; SINGH, Dr. Dept. of Library; Information Science, Gour University, Sagar (M.P.), India, Hari (BIBLIOPOLIS, 2020)
Virtual reference service is an emerging trend of traditional reference service. This pa-per describes some of the rising trend in digital reference services, including e-mail and web forms, text-based chat services; web-camera based services, ask-a-librarian services, digital robots, and collaborative services. It’s also discusses about basic concept, elements of Virtual reference service and give in detail modes, the advantages, disadvantages and limita-tions.